2005
DOI: 10.1038/sj.sc.3101774
|View full text |Cite
|
Sign up to set email alerts
|

Body weight supported treadmill training in acute spinal cord injury: impact on muscle and bone

Abstract: Design: Longitudinal prospective case series. Objective: To evaluate the impact of early introduction postspinal cord injury (SCI) of twiceweekly body-weight supported treadmill training (BWSTT) on muscle and bone. Setting: Centre for Health Promotion and Rehabilitation, McMaster University, Canada. Methods: Five individuals who had sustained traumatic SCI within 2-6 months participated in the study. Bone mineral densities (BMD) of proximal femur, distal femur, proximal tibia and lumbar spine were measured bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 45 publications
3
75
1
6
Order By: Relevance
“…In one study, there was an increase of 4.9% in thigh muscle area and 8.2% in the lower leg after 12 months of gait training (three times a week, totaling 144 sessions) without NMES; however, this study included only incomplete spinal cord injuries, paraplegia and quadriplegia [14]. A reversal of muscle atrophy in acute patients with incomplete quadriplegia (American Spinal Cord Injury Association B and C) after 48 sessions of treadmill gait training twice a week also was reported [13]. Stewart et al [24] reported an increase in size of Types I and IIa fibers with restoration of the normal size of muscle fibers after 6 months of gait (68 sessions) without NMES beginning with 65% ± 3% and ending with 23% ± 5% of BWS in individuals with incomplete (American Spinal Cord Injury Association C) paraplegia and quadriplegia.…”
Section: Discussionmentioning
confidence: 82%
“…In one study, there was an increase of 4.9% in thigh muscle area and 8.2% in the lower leg after 12 months of gait training (three times a week, totaling 144 sessions) without NMES; however, this study included only incomplete spinal cord injuries, paraplegia and quadriplegia [14]. A reversal of muscle atrophy in acute patients with incomplete quadriplegia (American Spinal Cord Injury Association B and C) after 48 sessions of treadmill gait training twice a week also was reported [13]. Stewart et al [24] reported an increase in size of Types I and IIa fibers with restoration of the normal size of muscle fibers after 6 months of gait (68 sessions) without NMES beginning with 65% ± 3% and ending with 23% ± 5% of BWS in individuals with incomplete (American Spinal Cord Injury Association C) paraplegia and quadriplegia.…”
Section: Discussionmentioning
confidence: 82%
“…In people with acute SCI, lean mass is only 60-65% that of able-bodied controls and body fat can increase to levels corresponding to 100-113% of that of controls. 15 Reduced muscle mass and increased fat mass are both considered risk factors for secondary health complications and chronic disease.…”
Section: G3mentioning
confidence: 99%
“…17 Lean (muscle) and fat mass: Two level 4 studies examined body composition changes. Giangregorio et al 15 examined the effects of a 2 Â per week body-weight-supported treadmill training (BWSTT) program and reported increases in thigh and calf muscle cross-sectional area (4-57%) and increased leg fat. Another study involving arm ergometry showed no significant changes in lean or fat mass.…”
Section: Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…BWST training involves assisted walking while supported over a treadmill by a harness mechanism and overhead pulley system that can support a percentage of the participant's body weight. It has been shown to improve ambulation, 11,12 partially reverse muscle atrophy, 13 improve whole body lean mass 14 and muscle morphology, 15 improve heart rate and blood pressure variability, and increase femoral artery compliance 16,17 after SCI. Tilt-table standing (TTS) is an alternative weight-bearing training technique, which is less labor intensive than BWST training.…”
Section: Introductionmentioning
confidence: 99%